PEMETAAN ZONA GEOMORFOLOGI EKOSISTEM TERUMBU KARANG MENGGUNAKAN METODE OBIA, STUDI KASUS DI PULAU PARI - Anggoro, Ari; Siregar, Vincentius P.; Agus, Syamsul B. (Institut Teknologi Sepuluh Nopember, 2015)
This study used object-based image analysis (OBIA) for geomorphic zones map of coral reef ecosystem in Pari Islands. The application of OBIA methods was used multiresolution segmentation algorithm with different scale parameter for each level. Classification methods for level 1 and 2 were used contextual editing classification. The results showed an overall accuracy for level 1 was 97% (reef level) and level 2 was 87% (geomorphic zone). Thus OBIA methods can be used and well-defined as an alternative for geomorphic zones map in other regions.